Most common, real life factors affecting effectiveness of omalizumab asthma treatment: a 10-year study - Jasmina Nurkić; Mona Al-Ahmad; Ahmed Maher; Nermina Arifhodžić; Edin Jusufović (Medicinski glasnik, 2018)
Aim: To assess efficacy of omalizumab in moderate to severe asthma and notable factors affecting it, such as treatment compliance during the period of ten years. This retrospective, observational real life study is the first of this kind in the Gulf region and one of the worldwide rare long term omalizumab treatment studies. Methods: The treatment for 35 patients started in 2008. Twenty patients (ongoing group) proceeded with treatment and were assessed annually until 2017. Reasons for treatment discontinuation in 15 patients (drop-out group) were also assessed. Results: Before starting omalizumab the ongoing group of patients had history of ?2 asthma exacerbations per year, which significantly decreased during the first year of the treatment (p<0.001), and for 14 (70%) patients ?1 exacerbation stayed during the next 10 years. Since 2014 six (30%) patients had had ?2 annual asthma exacerbations (p<0.05 in 2013; p<0.05 in 2014; p<0.001 in 2015; p<0.01 in 2016; p<0.001 in 2017). At the same time there was a significant drop in compliance index (CI) (p<0.0001). Conclusion: To our knowledge this is the first 10-year study of compliance and effectiveness, which may help finalize some practical suggestions to improve CI in clinical practice and to note acceptable variation in CI. It is important to recognize factors that can possibly affect effectiveness of the treatment and identify the patients who will have the best benefit from a long term omalizumab treatment.
Keywords: omalizumab; compliance; efficacy; long term